2021
DOI: 10.32677/ijch.2021.v08.i01.010
|View full text |Cite
|
Sign up to set email alerts
|

Duhamel’s procedure for Hirschsprung’s disease and the functional outcome in a tertiary care center

Abstract: Introduction: Hirschsprung’s disease (HD) is a developmental disorder caused by the migration failure of neural crest cells during intestinal development, resulting in an aganglionic colon and causing a functional obstruction in children. Duhamel’s procedure (DP) which involves excision of the aganglionic segment with retrorectal pull through, and anastomosis of the ganglionated bowel above dentate line, is one of the classical surgical procedures for HD. Materials and Methods: This retrospective study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In our study intestinal obstruction was found in 11.11% in male while 12% in female children. As compared with another study Intestinal obstruction was found in 5.8% patients [16]. In our study enterocolitis was found in 50.7% Patients.…”
Section: Discussionsupporting
confidence: 54%
“…In our study intestinal obstruction was found in 11.11% in male while 12% in female children. As compared with another study Intestinal obstruction was found in 5.8% patients [16]. In our study enterocolitis was found in 50.7% Patients.…”
Section: Discussionsupporting
confidence: 54%
“…In particular, the TAEPT technique may have certain advantages over the transabdominal Soave and Duhamel operations. 26,27 Commonly used procedures include TAEPT, Soave, and Duhamel. 26,28 Fourteen patients who received definitive surgery received treatment with the TAEPT procedure, and Duhamel treated 7 patients each (Table 2).…”
Section: Discussionmentioning
confidence: 99%